Physiological profile of best Czech male and female young triathletes - Bunc, V.; Heller, J.; Horcic, J.; Novotny, J. (The Journal of Sports Medicine and Physical Fitness, 1996)
To characterize the physiological profile of top young triathletes, 13 top female (mean age = 17.1 +/- 1.4 years, body mass = 58.8 +/- 4.7 kg, body height = 168.4 +/- 2.0 cm and body fat = 10.4 +/- 2.6%) and 23 top male triathletes (age = 17.7 +/- 2.2 years, mass = 66.7 +/- 7.1 kg, height = 176.5 +/- 5.1 cm and fat 8.2 +/- 2.3%) were evaluated by means of an incremental exercise (increment was 1 km.h-1, and exercise starting at 11 km.h-1 in females and 13 km.h-1 in males) on a treadmill with 5% inclination. Mean VO2max was 67.9 +/- 5.9 ml.kg-1 min-1 in boys and 56.1 +/- 2.4 ml.kg-1.min-1 in girls. mean value of maximal running speed was 18.6 +/- 1.2 km.h-1 in mean and 15.4 +/- 0.6 km.h-1 in females and LAmax was 12.5 +/- 2.3 mmol.l-1 in boys and 12.6 +/- 1.2 mmol.l-1 in girls. The selected functional variables at ventilatory threshold (VT) level in boys and girls corresponded to VO2max.kg-1 56.0 +/- 5.4 and 46.6 +/- 2.6 ml.kg-1.min-1, respectively, %VO2max.kg-1 at VT 82.4 +/- 2.1 and 83.1 +/- 1.7%, respectively, speed of running 15.2 +/- 1.4 and 12.7 +/- 0.7 km.h-1, respectively, %Vmax at VT 81.8 +/- 2.6 and 82.3 +/- 1.6%, respectively and the coefficient of energy cost of running c was 3.74 +/- 0.42 and 3.71 +/- 0.39 J.kg-1.m-1, respectively. A comparison of the functional profiles of these triathletes with elite young athletes from the sports of swimming (age 17.5 +/- 2.0 and 17.2 +/- 1.7 years, respectively, VO2max 61.6 +/- 3.6 and 52.1 +/- 3.6 ml.kg-1. min-1, respectively, Vmax 17.5 +/- 0.8 and 15.0 +/- 0.9 km.h-1, respectively, LAmax 11.1 +/- 3.2 and 11.8 +/- 3.3 mmol.l-1, respectively) cycling (17.7 +/- 1.8-17.0 +/- 1.7 years; 65.4 +/- 5.1-55.1 +/- 2.4 ml.kg-1. min-1, 18.2 +/- 0.7-15.2 +/- 0.8 km.h-1; 13.3 +/- 3.5-12.9 +/- 3.7 mmol.l-1) and middle-distance running (17.8 +/- 1.9-17.2 +/- 2.1 years; 66.8 +/- 4.7-57.3 +/- 2.6 ml.kg-1.min-1, 19.1 +/- 0.9-16.1 +/- 0.9 km.h-1; 13.1 +/- 2.6-13.7 +/- 3.0 mmol.l-1) showed the physiological characteristics of triathletes to be similar to those of middle-distance runners. According to our results and according to the data from the literature we can conclude that physiological predispositions for success in international triathlon may be as follows in boys and girls: VO2max.kg-1 higher than 65 and 60 ml.kg-1 min-1, respectively, Vmax (5%) higher than 18 and 16 km.h-1, respectively, LAmax higher than 12 and 11 mmol.l-1, respectively, running speed at "anaerobic threshold" higher than 15.0 and 13 km.h-1, respectively, %VO2max at "anaerobic threshold" level higher than 82.5% in both sexes, and the coefficient of energy cost of running lower than 3.75 and 3.73 J.kg-1.m-1, respectively. As in other sports events of an endurance native, these data are not the sole predictor of racing success. Nevertheless these standards are necessary but not sufficient conditions for success in triathlon. These data play a decisive role in the selection of talent for the triathlon.